IMPLEMENTASI GAYA KEPEMIMPINAN KEPALA SEKOLAH DEMOKRATIK DALAM MENGEMBANGKAN SEKOLAH EFEKTIF DI SD MUHAMMADIYAH 16 KARANGASEMTAHUN PELAJARAN 2016/2017 - Ambarwati, Ita; , Drs.Mulyadi Sri Kamulyan, SH, M.Pd (2017)
This study aims to determine: 1) To know the implementation of leadership style Principal Type Democratic in SD Muhammadiyah 16 Karangasem, 2) To describe the efforts undertaken Principal to develop schools Effective in SD Muhammadiyah 16 Karangasem, 3) To identify the obstacles encountered by the Head school when implementing the Democratic leadership style mode in developing Effective schools. The research is a qualitative research design case study (Case Studies). The informants are principalsand teachers. Data collection techniques used were observation, interviews and documentation. Data analysis through data collection, data reduction and conclusion / verification. Mechanical data validity checking is done by methods triangulation and source triangulation. The results showed the deliberations at the school, the moment of decision, their efforts to provide a letter of invitation and extracurricular to create effective schools and quota restrictions when the new student enrollment to implement a Leadership Style Headmaster Democratic in developing effective schools in SD Muhammadiyah 16 Karangasem in Lesson 2016/2017.